Measurement and correlation of physicochemical properties of phosphonium-based deep eutectic solvents at several temperatures (293.15 K–343.15 K) for CO2 capture - Ghaedi, H. (Academic Press, 2017)
Recently, deep eutectic solvents (DESs) as the new solvents have received considerable amount of attention between researchers in different research fields and are under investigation so find out their potential to become a versatile alternative to ionic liquids (ILs) and traditional solvents. DESs are derived from two or more salts as the hydrogen bond acceptors (HBAs) and hydrogen bond donors (HBDs). Six DESs were synthesized namely allyltriphenylphosphonium bromide- diethylene glycol (ATPPB-DEG) and allyltriphenylphosphonium bromide- triethylene glycol (ATPPB-TEG) using three mole ratios of 1:4, 1:10 and 1:16 salt to HBDs. In this work, we report physicochemical properties of these DESs, which include density, molar volume, isobaric thermal expansion, refractive index, specific refraction, molar refraction, free molar volume, electronic polarization and internal pressure at several temperatures from 293.15 K to 343.15 K. Most of these properties are fitted to a linear equation by the method of least-squares using the Levenberg-Marquardt algorithm to derive the corresponding parameters and estimate the root mean square error (RMSE) and least squared correlation coefficient (R2). © 2017